Structure, Narrative Context, and Function of Healing Mantras in Biaro Baru Village, North Musi Rawas Regency, Indonesia - Yeni Oktariyani; Siti Rukiyah; Sri Wahyu Indrawati (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the structure, narrative context, and function of healing mantras in Biaro Baru Village, Karang Dapo District, North Musi Rawas Regency, Indonesia. Using a qualitative descriptive method, data were collected through observation, in-depth interviews, and documentation from five informants (traditional healers/shamans) who actively use mantras in healing practices. Five healing mantras were recorded, transcribed, translated, and analyzed. The analysis focused on linguistic structure (using frameworks of oral literature analysis), narrative context (using Dell Hymes’ SPEAKING model), and social-cultural function. Results reveal that the healing mantras exhibit four structural elements: (1) rhyme (end-rhyme and initial-rhyme patterns); (2) rhythm (repetitive syllabic patterns creating a hypnotic quality); (3) repetition (of words, phrases, and sounds for emphasis and magical effect); and (4) distinctive diction (archaic words, code-switching between Musi Malay and Arabic). The narrative context is governed by strict norms regarding setting (typically at the patient’s home or specific ritual sites), timing (often at night or specific hours), participants (healer, patient, sometimes family members), and ritual preparations (offerings, water, specific objects). The mantras serve multiple complementary functions: magical-religious (invoking divine power for healing), therapeutic (providing psychological comfort to patients), social (reinforcing the healer’s role and community bonds), and cultural (preserving and transmitting local wisdom). This study contributes to the documentation of endangered oral traditions in Indonesia and provides a model for analyzing similar oral literature forms.